Callus formation, somatic embryogenesis and development of transformation protocol by practicle bombardment in plantain banana - Deswina, Puspita (2001)
The plantain bananas are among the most valued crop plants in the tropical world. However, the commercially attainable yields are very low compared to dessert bananas. Conventional breeding of this plant remains a difficult endeavor because of high sterility and polyploidy; therefore, the integration of biotechnology into plantain improvement programmes is essential. Somatic embryogenesis has the great potential for rapid and efficient regeneration of plantlets and offers opportunities for large-scale production of plant material. The yield and quality of somatic embryos produced in cell culture depends on the media constituents and explants type. In this study, in vitro rhizomes initiated from shoot tips (8 week-old cultures) of cultivars Nangka and Tanduk and immature male flowers of cultivar Nangka were used as explants. The results of callus initiation showed that treatments with 2,4-D, Picloram and Dicamba produced callus ranging from 0.0-82.0% for cultivar Nangka and 0.0-58.0% for cultivar Tanduk. The type of callus varied depending on concentrations of PGRs used for the initiation. However, no callus formation was obtained from the auxin-free medium. The study on the determination of callus growth curve showed that treatments with 2,4-D and Picloram for both cultivars Nangka and Tanduk produced a sigmoidal pattern, except for several concentrations which failed to show the callus growth pattern. Whereas, for the Dicamba treatments, there was no callus growth at all. The effects of two basal media supplemented with 2,4-D and Picloram at different concentrations were studied. The highest callus fresh weight (0.37 g) was attained on SH medium plus 2.5 µM Picloram. The effect of 2,4-D and Picloram in combination with other auxins and cytokinins, showed that there was no constant trend on callus growth in response to the treatments. However, the treatments using 2,4-D and Picloram in combination with other cytokinins produced nodular and compact callus. The callus produced embryogenic structure (13.3-66.7%) in the somatic embryogenesis medium, but no shoot regeneration was achieved, instead only roots were formed. In the initiation of callus from immature male flowers, 49.7% of flower cluster responded to form globular embryogenic callus and the highest response was from flower of rows 12 and 13 (60%). The study on the development of transformation protocol by particle bombardment using in vitro rhizome slices and embryogenic callus as explants and GFP fluorescent gene as the reporter gene revealed an unstable transient expression in the cell.